The effect of disaggregate information on the expectation formation of firms - Lukas Buchheim; Sebastian Link (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2017)
This paper studies a new aspect of firms' expectation formation by asking whether expectations primarily reflect aggregate, industry-wide information (e.g., industry trends) or disaggregate information (e.g., firm-specific information). First, we show that disaggregate information is strongly associated with expectations even when controlling for aggregate information at high-dimensional industry levels. Moreover, aggregate and disaggregate information explain comparable shares of the variance in expectations. Second, we exploit a natural experiment to identify the causal effect of new information on expectations. The predictable demand effects for durable goods due to the German VAT increase of 2007 implied that, at the time, durable goods retailers had access to more reliable information about their future demand than non-durable goods retailers. Utilizing this observation in a difference-in-differences design, we find that "treated" firms were significantly more forward-looking ahead of the VAT-induced demand shifts. Overall, our results suggest that firms rationally incorporate disagreggate information into their expectations.
urn:nbn:de:bvb:19-epub-41214-3
Keywords: D84; D22; E20; E32; E65; 330; Expectation Formation; Firm Behavior; Survey Data; Natural Experiments in Macroeconomics; Heterogeneity in Expectations